Cyberpunk in a transnational context (2019)
Since the inception of cyberpunk in the early 1980s, which coincided with the dawn of the Internet and the rise of computer hackers, the movement, with William Gibson as super star and Bruce Sterling as theoretical chairman, has consistently created a tremendous impact on today’s literature and culture, ranging from manga and anime to cinema. William Gibson’s 1980s Cyberspace Trilogy (Neuromancer [1984], Count Zero [1986], and Mona Lisa Overdrive [1988]), which explored the frontier of cyberspace—another name for the Internet coined by the same author—was followed by his 1990s “Bridge Trilogy” (Virtual Light [1993], Idoru [1996], and All Tomorrow’s Parties [1999]) featuring a virtual idol Rei Toei, without whom no AI Beauty (such as Hatsune Miku) could have been created. However, here we should reconsider the extraterritorial status of Gibson, who immigrated from South Carolina to Toronto, Canada, to evade the draft. Being a typical outsider, Gibson put special emphasis on the Lo-Tek spirit of a countercultural tribe in the post-apocalyptic near-future, and replace the keyword “steampunk” with “post-apocalypse”. This was to be shared by the punk kids that Otomo describes in Akira and the human weapons distinguished director Shinya Tsukamoto represents in his TETSUO trilogy (1989–2010), one of the major inheritors of the Japanese Apache created by Komatsu Sakyo, a founding father of Japanese science fiction, in his first novel Nippon Apacchi-zoku (The Japanese Apache [1964]) as I detailed in Full Metal Apache (Duke UP, 2006). A further descendant of cyberpunk could well be easily noticed in Neil Blomkamp’s South African post-cyberpunk film, District 9 (2009), in which the natives of Johannesburg and the miserable aliens lost in space turn out to have the Lo-Tek spirit in common. Yes, cyberpunk is a literary and (sub-)cultural subgenre not so much celebrating the growth of high-technology as the neo-extraterritorial spirit of Lo-Tek tribes born out of postmodern streets. What matters now is that, in this context, cyberpunk has started gaining new significance, not only in today’s arts of representation, but also in international/transnational politics. The present collection of essays showcases a diversity of cyberpunk possibilities ranging from Cool Japan, Dystopian narrative down to the postmodern extraterritorial and Anthropocene.